Good practices in the prevention of driving under the influence of alcohol - Marín Picado, Bradly (2014)
Fifty percent of the morbi-mortality related to traffic accidents is associated to alcohol consumption. In Costa Rica, during the last three decades, the amount of traffic accidents in which at least one person has been under alcohol influence had grown. This paper contains an analysis of the achievements and limitations of the preventive campaigns in our country and a review of international literature about prevention models that had demonstrated their efficacy in this topic.